2014
DOI: 10.1186/1471-2458-14-813
|View full text |Cite
|
Sign up to set email alerts
|

Annual public health and economic benefits of seasonal influenza vaccination: a European estimate

Abstract: BackgroundVaccination is currently the most effective means of preventing influenza infection. Yet evidence of vaccine performance, and the impact and value of seasonal influenza vaccination across risk groups and between seasons, continue to generate much discussion. Moreover, vaccination coverage is below recommended levels.MethodsA model was generated to assess the annual public health benefits and economic importance of influenza vaccination in 5 WHO recommended vaccination target groups (children 6 – 23 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 28 publications
4
104
0
11
Order By: Relevance
“…Although vaccine distribution is only a crude measure of vaccine uptake, the findings from this study agree with those of a Europeanwide survey of the influenza vaccination Venice II project [1,2], which show that the uptake rate for at-risk populations is still well below the WHO-recommended target of having 75% covered.…”
Section: Commentarysupporting
confidence: 79%
See 3 more Smart Citations
“…Although vaccine distribution is only a crude measure of vaccine uptake, the findings from this study agree with those of a Europeanwide survey of the influenza vaccination Venice II project [1,2], which show that the uptake rate for at-risk populations is still well below the WHO-recommended target of having 75% covered.…”
Section: Commentarysupporting
confidence: 79%
“…Although the large variability in study outcomes may offer room for scientific debate about the "true" vaccine effectiveness in any particular year and geographical area, overall, the benefits of influenza vaccination are well documented [2,3] and form the scientific basis for current policy recommendations. Because overall, the influenza vaccines in the USA and Europe are the same, vaccine effectiveness cannot explain the disparity in trends of vaccine distribution rates in the 2 respective continents.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Describing these studies in detail goes beyond the scope of this review, however, studies modeling the impact of vaccination have unequivocally shown that vaccines are critical to the reduction of influenza-related illness and healthcare costs, and that the benefits of vaccination outweigh the costs. [4][5][6][7] This article reviews the current status of cell culture-based influenza vaccine platform, its advantages and drawbacks, and the future of influenza vaccine research.…”
Section: Introductionmentioning
confidence: 99%